2015
DOI: 10.3928/1081597x-20150424-08
|View full text |Cite
|
Sign up to set email alerts
|

Vector Analysis of 1-Year Astigmatic Outcomes From a Prospective, Randomized, Fellow Eye Comparison of Wavefront-Guided and Wavefront-Optimized LASIK in Myopes

Abstract: WFG-LASIK and WFO-LASIK using the Alcon WaveLight Allegretto Eye-Q 400-Hz excimer laser platform produce similar astigmatic results in myopic patients; however, the WFG mode may produce slightly more predictable astigmatic corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The slightly larger (nonsignificant; p = 0.078) DV values in the WFO group may have been related to the higher values of the absolute AofE. A previous study reported absolute AofE values of 1.9 ± 0.67 for WFG LASIK and 9.7 ± 3.70 for WFO LASIK, with a significant group difference; however the groups did not differ in DV, CI, IOS, and MofE [ 14 ]. Kalifa and colleagues also reported that the AofE is significantly better in moderate myopic eyes after WFG LASIK; furthermore, WFG LASIK showed significantly better results in DV, CI, and MofE compared to that for WFO LASIK [ 16 ].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The slightly larger (nonsignificant; p = 0.078) DV values in the WFO group may have been related to the higher values of the absolute AofE. A previous study reported absolute AofE values of 1.9 ± 0.67 for WFG LASIK and 9.7 ± 3.70 for WFO LASIK, with a significant group difference; however the groups did not differ in DV, CI, IOS, and MofE [ 14 ]. Kalifa and colleagues also reported that the AofE is significantly better in moderate myopic eyes after WFG LASIK; furthermore, WFG LASIK showed significantly better results in DV, CI, and MofE compared to that for WFO LASIK [ 16 ].…”
Section: Discussionmentioning
confidence: 92%
“…WFO and WFG treatments have mainly been evaluated with regard to visual acuity, correction of refractive errors, and HOAs; few studies have compared the treatments using astigmatism vector analysis [ 14 16 ]. Furthermore, an evaluation of astigmatic correction in patients with moderate to high astigmatism and a comparison of WFG and WFO profiles in trans-PRK were lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…analyzed outcomes of a randomized fellow eye comparison of WFO and WFG LASIK and reported higher AofE values in the WFO group. 13 The latter authors compared WFO and WFG PRK outcomes of fellow eyes over 1 year and reported higher AAofE in the WFO group but similar MofE between the groups. 14 …”
Section: Discussionmentioning
confidence: 95%
“…Although both platforms consider preoperative wavefront analysis of the eye, some investigators have proposed that WFG profile may be superior to WFO in myopic and astigmatic correction, reflecting the individualized nature of the former. 12 13 14 15 However, the majority of the evidence in this area comes from laser-assisted in situ keratomileusis (LASIK), not PRK, patients. On the other hand, only few studies have considered the astigmatic vector analysis of patients with moderate-to-high astigmatism in their study designs.…”
Section: Introductionmentioning
confidence: 99%